29.7k views
0 votes
Q3) f(x) 2x^2 - 5x, g(x) = 3x^3 find g(4x)

User Yissy
by
4.6k points

1 Answer

2 votes

Answer:

g(4x) = 192x^3

Explanation:

For this problem, f(x) is irrelevant since we are simply are dealing with g(x). We will simply replace the value of x in g(x) with 4x. So let's do that.

g(x) = 3x^3

g(4x) = 3(4x)^3

g(4x) = 3(4^3)(x^3)

g(4x) = 3(64)(x^3)

g(4x) = 192x^3

Hence, g(4x) is 192x^3.

Cheers.

User Jstromwick
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.